Implementation of the 'Sapere Migliora' information aid for newly diagnosed people with multiple sclerosis in routine clinical practice: a late-phase controlled trial. (August 2014) - Giordano, A; Lugaresi, A; Confalonieri, P; Granella, F; Radice, D; Trojano, M; Martinelli, V; Solari, A; ,
Background: The SIMS-Trial showed that the 'Sapere Migliora' information aid (IA) for newly diagnosed people with multiple sclerosis (PwMS) effectively improved patient knowledge and satisfaction with care. Objectives: The objectives of this paper are to assess the effectiveness of the IA in clinical practice and to compare the whole IA with the take-home booklet/website component alone. Methods: After updating the IA and replacing the CD with a website, a prospective, open-label non-randomised controlled trial compared the whole IA (group A, five SIMS-Trial centres) to take-home (group B, 16 centres). One month after the intervention, participants completed the MS Knowledge Questionnaire (MSKQ), care satisfaction questionnaire (COSM-R) (primary study outcomes), Hospital and Anxiety Depression Scale, and ad hoc questionnaire appraising the IA. Results: We enrolled 159 newly diagnosed PwMS (May 2012–March 2013). Drop-outs were four of 77 (5%, group A) and 11/82 (13%, group B). Primary endpoint (highest tertile both for MSKQ and COSM-R section 2 scores) was achieved by 38/77 (49%) group A and 33/82 (40%) group B ( p = 0.25). Attainment of secondary outcomes was also similar between groups. Conclusions: This study shows that the entire IA is not superior to the booklet/website alone, and that both are comparable in efficacy to the intervention arm of the SIMS-Trial. Trial registration number: ISRCTN78940214.